2010
DOI: 10.1186/1471-2458-10-434
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anthropometric characteristics in pregnancy and blood pressure among adolescents: 1993 live birth cohort, Pelotas, southern Brazil

Abstract: BackgroundWe investigated the association between maternal anthropometric measurements in prepregnancy and at the end of pregnancy and their children's systolic (SBP) and diastolic (DBP) blood pressure at 11 years of age, in a prospective cohort study.MethodsAll hospital births which took place in 1993 in the city of Pelotas - Brazil, were identified (5,249 live births). In 2004, the overall proportion of follow-up was 85% and we obtained arterial blood pressure measurements of 4,452 adolescents.ResultsIndepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
4
9
0
2
Order By: Relevance
“…Compared with childhood adiposity/BMI, the relationship between maternal BMI and childhood cardiovascular function has infrequently been addressed and is almost exclusively confined to measurement of blood pressure; however, several mother–child cohort studies now report independent relationships between maternal BMI and blood pressure in older children and adolescents (Laura et al . , Filler et al . , Wen et al .…”
Section: Epidemiological Evidence Supporting the Developmental Programentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with childhood adiposity/BMI, the relationship between maternal BMI and childhood cardiovascular function has infrequently been addressed and is almost exclusively confined to measurement of blood pressure; however, several mother–child cohort studies now report independent relationships between maternal BMI and blood pressure in older children and adolescents (Laura et al . , Filler et al . , Wen et al .…”
Section: Epidemiological Evidence Supporting the Developmental Programentioning
confidence: 99%
“…Maternal pre-pregnancy obesity vs. GWG and cardiovascular risk of offspring Compared with childhood adiposity/BMI, the relationship between maternal BMI and childhood cardiovascular function has infrequently been addressed and is almost exclusively confined to measurement of blood pressure; however, several mother-child cohort studies now report independent relationships between maternal BMI and blood pressure in older children and adolescents (Laura et al 2010, Filler et al 2011, Wen et al 2011, Hochner et al 2012. A recent study has also observed that maternal pre-pregnancy obesity/ overweight is associated with increased systolic blood pressure (SBP) in 7-year-old children (Wen et al 2011).…”
Section: Maternal Obesity and Offspring Cardiovascular Riskmentioning
confidence: 99%
“…Smoking and BMI in the women of the second generation might affect the outcome of the study. 18,19 However, both these covariates were only available in Sweden for women being pregnant in 1992 or later (n = 397 063). In a supplementary analysis, we only included women from the Swedish MBR that gave birth in 1992 or later, where data on smoking habits as well as BMI were available (n = 353 976).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking and BMI in the women of the second generation might affect the outcome of the study . However, both these covariates were only available in Sweden for women being pregnant in 1992 or later ( n = 397 063).…”
Section: Methodsmentioning
confidence: 99%
“…Indian women are by nature shorter than peers elsewhere and the 'maternal constraint' imposed by physical stature (shorter height), pelvic size and lifetime reserves of metabolic substrates can impact the next generation through effects on offspring birth size, linear growth and future biomarkers for metabolic disease 22,51,52 . Pre-pregnancy maternal weight, weight gain during pregnancy and own birth weight of the parents are all shown to be positively associated with offspring birth weight, body composition and insulin resistance in childhood and later life 12,[52][53][54][55][56] .…”
Section: Parental Body Sizementioning
confidence: 99%